Ethics and Burial Archaeology. - Sayer, Duncan (Debates in Archaeology Ser., 2010)
The investigation of human remains has always been central to archaeological, but archaeologists are not the only ones with an interest in their treatment. This book sets a fresh agenda for ethical studies in mortuary investigation, adducing a series of case studies which can be used to understand the questions facing burial archaeology.